2011
DOI: 10.1186/1475-2875-10-309
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood group with severe falciparum malaria in adults: case control study and meta-analysis

Abstract: BackgroundErythrocyte-associated antigenic polymorphisms or their absence have perhaps evolved in the human population to protect against malarial infection. Studies in various populations consistently demonstrate that blood group 'O' confers resistance against severe falciparum infection. In India, Odisha state has one of the highest incidences of Plasmodium falciparum infection and contributes to the highest number of deaths by falciparum malaria. This study aims to evaluate the relationship between ABO bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 30 publications
12
66
3
4
Order By: Relevance
“…These authors also said that blood group A had a greater risk of developing severe Pf malaria. In our study, blood group B dominated the complicated Pf cases (63.6%), coinciding with studies by Panda AK et al (12) , followed by blood group O. But this was not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
“…These authors also said that blood group A had a greater risk of developing severe Pf malaria. In our study, blood group B dominated the complicated Pf cases (63.6%), coinciding with studies by Panda AK et al (12) , followed by blood group O. But this was not statistically significant.…”
Section: Discussionsupporting
confidence: 79%
“…Questions still remain unanswered about the interactions between malaria parasites and other blood group antigens [45]. Panda et al, in India observed that the protective role of the blood group O and susceptibility of the blood group B to severe disease; and in a further meta-analysis of 19 relevant studies on falciparum malaria and the ABO blood group, the same findings of protection provided by the blood group O was noted but with susceptibility to the A and AB blood groups [43].…”
Section: Duffy Antigenmentioning
confidence: 62%
“…It has also been demonstrated that the blood group O provides some protection against severe falciparum malaria [41][42][43][44]. This protective effect of blood group O operates through the mechanism of reduced P. falciparum rosetting (binding of infected to uninfected erythrocytes) [41,44].…”
Section: Duffy Antigenmentioning
confidence: 99%
“…Importantly, there is still debate on this issue (6,18). In the study by Meyer (19), norovirus infection was the most common among individuals with blood group O.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between blood groups and some infections such as norovirus, cholera, malaria, and Crimean-Congo fever has been reported (3,5). Some other studies have proposed that there is some relationship between blood type and severity of diseases (6). In addition, the relationship between blood groups and some diseases such as chronic urinary tract infections has been studied (7), but such a relationship has not been shown in other studies (8).…”
Section: Introductionmentioning
confidence: 99%